Pelatihan Aplikasi Sarana Pemasaran Online Imooji Untuk Mitra Produk Gusereen di Masa Pandemi Covid-19 - Latifa Hanum; Regia Indah Kemala Sari; Riva Hendriani; Siska Fitrianti (Institut Pertanian Bogor, 2021)
Marketing of palm sugar products in District of Lima Puluh Kota is still managed traditionally, rarely use online marketing. Product marketing of Gusereen still relies on word of mouth and the limited use of groups on social media. This training activity aims to provide knowledge on how to make imooji digital brochures to increase promotion and sales of Gusereen products. The collection of data and information is conducted by observing and interviewing the needs and situations experienced by partners, business processes and obstacles faced. Training method is using the PLA (Participatory Learning and Action) method. Exposure of lesson materials to partners is conducted by providing information on the use of imooji, the choice of packages provided, and how to use imooji. Participants get lesson learn and guidance through the direct practices of using the application. The training practices carried out include 1) How to log in and register as a new user; 2) How to use the imooji user interface; 3) Choose a preferred and suitable template for Gusereen products; 4) Upload photos of the products; 5) Change text or product images; 6) Save and preview the created imooji; and 7) Publish or share imooji on social media. This training succeeded in increasing participants' knowledge by 45% from pre-test to post-test. Participants benefit from the training provided and 87% of participants understand the material provided. This training is expected to be the beginning of the transfer of knowledge and information to the palm sugar business community, especially for palm sugar business actors in Labuah Gunuang.